2023
DOI: 10.1039/d2ra06567c
|View full text |Cite
|
Sign up to set email alerts
|

Crystal defect induced zero thermal quenching β-NaYF4: Eu3+, Sm3+ red-emitting phosphor

Abstract: The mechanism of zero thermal quenching of β-NaYF4: 0.065Eu3+, 0.002Sm3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…The Eu 3+ and Yb 3+ are incorporated into the matrix. In our previous studies, we found that the down-conversion luminescent ions: Sm 3+ , Dy 3+ , and Tb 3+ lead to a decrease of thermal luminescent stability of Eu 3+ , despite the existence of an energy transfer effect. Therefore, we tried to utilize upconversion ion Yb 3+ to improve the ZTQ property of Eu 3+ in this study.…”
Section: Introductionsupporting
confidence: 87%
“…The Eu 3+ and Yb 3+ are incorporated into the matrix. In our previous studies, we found that the down-conversion luminescent ions: Sm 3+ , Dy 3+ , and Tb 3+ lead to a decrease of thermal luminescent stability of Eu 3+ , despite the existence of an energy transfer effect. Therefore, we tried to utilize upconversion ion Yb 3+ to improve the ZTQ property of Eu 3+ in this study.…”
Section: Introductionsupporting
confidence: 87%